1984
DOI: 10.1063/1.447508
|View full text |Cite
|
Sign up to set email alerts
|

The ν1 band of the DO2 radical by difference frequency laser and diode laser spectroscopy: The equilibrium structure of the hydroperoxyl radical

Abstract: The ν1 band of the DO2 radical was observed by difference frequency laser and diode laser spectroscopy with Zeeman modulation. The radical was produced by a 60 Hz discharge in a mixture of CH3OD or CD3OD and O2 flowing through a multiple reflection absorption cell. The observed lines, 181 in total, of six subbands with Ka =2←3, 1←2, 0←1, 1←0, 2←1, and 3←2 were included in a least-squares analysis to determine molecular parameters for the upper state: A=326 929.3(92), B=31 683.68(36), C=28 779.96(46), εaa=−26 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
47
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(58 citation statements)
references
References 28 publications
11
47
0
Order By: Relevance
“…This potential is not perfect, but should be good enough for our purposes. The correspondin~ equilibrium structure is r~ = 0.9716~,, R e = 1.3304 A and c~ = 104.307 °, in very close agreement with values derived from high-resolution spectroscopy [22,23]. Compared to our CCSD(T) calculations for HO2-, there is a substantial decrease of 0.192 A in the OO equilibrium bond length.…”
Section: I)ksupporting
confidence: 82%
See 1 more Smart Citation
“…This potential is not perfect, but should be good enough for our purposes. The correspondin~ equilibrium structure is r~ = 0.9716~,, R e = 1.3304 A and c~ = 104.307 °, in very close agreement with values derived from high-resolution spectroscopy [22,23]. Compared to our CCSD(T) calculations for HO2-, there is a substantial decrease of 0.192 A in the OO equilibrium bond length.…”
Section: I)ksupporting
confidence: 82%
“…Using the PEF of Bunker et al [20], the wavenumbers of the fundamentals for DO2 are calculated to be 1025.4 (1020.16), 1117.4 (1121.47) and 2550.3 (2549.22) cm -~, with experimental values [22,24,25] given in parentheses. The vibrational mode with lowest wavenumber is mostly DOO bending in character and will therefore be designated vz in order to maintain the analogy with HOe.…”
Section: I)kmentioning
confidence: 99%
“…Lubic et al, 1984Lubic et al, 1984Lubic et al, 1984Uehara et al, 1985Uehara et al, 1985Uehara et al, 1985 Weiner et al, 1986Weiner et al. 1986Weiner et al, 1986Weiner et al.…”
Section: Hydroperoxyl Radicalmentioning
confidence: 97%
“…Lubic et al (1984) reported the equilibrium geometry of the hydroperolryl radical in the ground state (,A'), and Table 1 displays the bond lengths and bond angle.…”
Section: Hydroperoxyl Radicalmentioning
confidence: 99%
“…18 The potential was forced to reproduce the experimental equilibrium geometry, 19 dissociation energy, 15 and quadratic force constants 4,20 of the hydroperoxyl radical. Again the vibrational information was included using the harmonic force field.…”
Section: Potential Energy Functionsmentioning
confidence: 99%